Simplify 9 X D X E X 6
📈a) expand and simplify. 9(x Simplify the polynomial, then evaluate for x=2. x=3x^2+2x-3-4x^2+6 Simplify polynomial evaluate 4x
Simplify the polynomial, then evaluate for x=2. x=3x^2+2x-3-4x^2+6
Simplify socratic How do you simplify ( x^3
![How do you simplify ( x^3 - x^2 - x +1)/(x^2 - 2x + 1)? | Socratic](https://i2.wp.com/useruploads.socratic.org/RnbJ73gUQDaieeB7zPti_mat1.jpg)
How do you simplify ( x^3 - x^2 - x +1)/(x^2 - 2x + 1)? | Socratic
![📈a) Expand and simplify. 9(x - 3) - 2(x-4) Simplify (9x-27)-(2x+8](https://i2.wp.com/us-static.z-dn.net/files/dc4/f99c0706d7c1148795c7f47ee2d81110.png)
📈a) Expand and simplify. 9(x - 3) - 2(x-4) Simplify (9x-27)-(2x+8
![Simplify the polynomial, then evaluate for x=2. x=3x^2+2x-3-4x^2+6](https://i2.wp.com/us-static.z-dn.net/files/d55/36e56d937ce905fd38e1406ab6f6b5af.png)
Simplify the polynomial, then evaluate for x=2. x=3x^2+2x-3-4x^2+6